2016
DOI: 10.1063/1.4940870
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of unemployment rates using small area estimation model by combining time series and cross-sectional data

Abstract: Labor force surveys conducted over time by the rotating panel design have been carried out in many countries, including Indonesia. Labor force survey in Indonesia is regularly conducted by Statistics Indonesia (Badan Pusat Statistik-BPS) and has been known as the National Labor Force Survey (Sakernas). The main purpose of Sakernas is to obtain information about unemployment rates and its changes over time. Sakernas is a quarterly survey. The quarterly survey is designed only for estimating the parameters at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…We expect that by adding time factor fixed effect we can improve the performance of the estimators. Moreover, Muchlisoh et al [4] as well as Sadik and Notodiputro [9] showed that incorporating time effects in SAE could improve the precision of the estimates.…”
Section: Introductionmentioning
confidence: 99%
“…We expect that by adding time factor fixed effect we can improve the performance of the estimators. Moreover, Muchlisoh et al [4] as well as Sadik and Notodiputro [9] showed that incorporating time effects in SAE could improve the precision of the estimates.…”
Section: Introductionmentioning
confidence: 99%
“…Estimates from an SAE model for the rotation group level, combined with the time-series multilevel model and the Rao-Yu model, have produced data to estimate a quarterly unemployment rate at the district level. aMuchlisoh et al 2015. Estimation of unemployment rate using small area estimation model based on a rotating panel national labor force survey.…”
mentioning
confidence: 99%